Deteksi Dini Tumbuh Kembang Anak dengan Metode Sistem Pakar dan Kuesioner Pra Skrining Perkembangan (KPSP) - Adhie Tri Wahyudi; Langgeng Vodka Riyanto; Ida Giyanti; Anita Indrasari (Program Studi Teknik Industri Universitas Setia Budi, 2019)
Psychology Bureau of Universitas Setia Budi (BP-USB) has a role in the life of the Surakarta city community as an officer carrying out child development checks using the KPSP form. Based on the results of interviews, BP-USB has obstacles in the process of examining the early childhood development, that the ineffectiveness of the inspection in terms of aspects: cost, energy and time. This study aims to build an early childhood development inspection based on android system using an expert system with the Forward Chaining Method based on KPSP to increase the effectiveness of examination time. The final results showed that the early childhood development expert system was able to shorten the examination time significantly. The effectiveness of examination time increased by 65%. Keywords: developmental pre-screening questionnaire, KPSP, expert system, forward chaining